From dream to reality: hope in the Sahel - Silva Soares, Horacio (Technical Centre for Agricultural and Rural Cooperation, 2001)
The World Food Summit held in Rome in November 1996 confirmed that access to food and the availability of food was still a major challenge. Soon, a little later than originally planned, the Summit s achievements will be reviewed, more than five...